Observation of topological Hall effect in antiferromagnetic FeRh film - Zhang, Sheng; Xia, Siyu; Cao, Qingqi; Wang, Dunhui; Liu, Ronghua; Du, Youwei (Applied physics letters, 2019)
Noncollinear magnetic structures can give rise to peculiar Hall effects and hold promise for next-generation spintronic devices. We report the observation of the topological Hall effect (THE) through electrical transport measurements in antiferromagnetic B2-ordered FeRh thin films grown by sputtering techniques on a MgO (001) substrate. Combining with the spin glass behavior below the metamagnetic transition temperature from ferromagnetism to antiferromagnetism, we ascribe THE to the emergence of noncollinear spin texture arising from the competitions among various exchange interactions in the antiferromagnetic state. This observation opens the possibility to discover the topological Hall effect in centrosymmetric antiferromagnets in contrast to the widely reported B20-type chiral magnets, promoting the application of antiferromagnets in spintronic devices.